2013
DOI: 10.1002/cssc.201200708
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanovoid Bi2WO6 2D Ordered Arrays as Photoanodes for Photoelectrochemical Water Splitting

Abstract: Herein we report a facile and economic method to prepare nanovoid Bi(2)WO(6) 2D ordered arrays employing a simple self-assembly procedure. The electrochemical properties and performance of the 2D nanoarray as a photoanode for water splitting are investigated and compared with a conventional photoanode of similar thickness. The 2D array photoanode shows a much higher photocurrent density and photon-to-H(2) conversion efficiency even with a small content of the Bi(2)WO(6) material. The enhancement is further stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 52 publications
2
58
0
2
Order By: Relevance
“…811 To a large extent, this interest originates from their relatively narrow bandgaps owing to the mixing of Bi 6s and O 2p orbitals, which leads to a cathodic shift in the position of the valence band. 12 …”
Section: Introductionmentioning
confidence: 99%
“…811 To a large extent, this interest originates from their relatively narrow bandgaps owing to the mixing of Bi 6s and O 2p orbitals, which leads to a cathodic shift in the position of the valence band. 12 …”
Section: Introductionmentioning
confidence: 99%
“…[89] Ac olloidal sphere array is used as at emplate, and this is followed by infiltration of the voids with as ol precursor.T he inverse opal structure is formedb yr emoving the templateb ye tching or calcination. [90] The 2D arrays lower the recombination rate by shortening the diffusion length for the holes, as depicted in Figure 7c-e. First, the precursor for the ternary metal oxide shouldb eh omogenously mixed in the molecular scale to achieve apure phase of the material.…”
Section: Bismuthtungstatementioning
confidence: 96%
“…[91] Bi 2 WO 6 showsH 2 evolution and poor oxygen evolution. [90] i-Bi 2 WO 6 and n-Bi 2 WO 6 correspond to inverse and opal Bi 2 WO 6 in panel b. Reproduced from Refs. Hill and Choi have synthesized Bi 2 WO 6 by thermal treatment of electrodeposited porous WO 3 .…”
Section: Bismuthtungstatementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [29] found that the porous Bi 2 WO 6 films offer a highly enhanced photocatalytic activity under illumination with visible light in comparison to the corresponding nonporous films. Other Bi 2 WO 6 nanocrystals with unusual activity, such as nanosheets [30,31], and nanovoid ordered arrays [32], nanofibrous mats [33] were reported. Nanosized photocatalysts have some superior property in aqueous photocatalytic reactions due to their large surface area, good dispersion, and etc.…”
Section: Introductionmentioning
confidence: 98%